Answer:
7x^2 - x -3
Step-by-step explanation:
(6x^2+3x) + (x^2 - 4x -3)
We have to use distributive property first to get rid of the parenthesis, so you simply have to multiply the positive (+) symbol with everything inside the second set of parenthesis.
+ * x^2 = x^2
+ * -4x = -4x
+ * -3 = -3
Now, we rewrite the equation which is
6x^2 + 3x + x^2 - 4x -3
Now you simply combine like terms.
6x^2 + x^2 = 7x^2
3x-4x = -x
The answer will be
7x^2 - x -3
Hope this helps!!
-Ketifa
(Can I get brainliest?)